Single-site organochromium catalysts: synthesis, characterisation by paramagnetic NMR and olefin polymerisation - Enders, Markus (Olefin polymerization, 2006)
Chromium(III)-complexes with monoanionic spectator ligands allow the preparation of highly active catalysts for ethylene polymerisation. We summarize the synthesis and NMR-spectroscopic investigations of precatalysts with quinolyl-functionalised Cp-ligands. These complexes have advantageous properties. For spectroscopic investigations the rigidity of the ligand framework helps to identify the species present in solution as fewer conformers are possible. For the application as polymerisation catalysts the high stability of the activated catalyst is important. We obtained meaningful analytical data by paramagnetic NMR, combined with DFT-calculation of the spin-density. These and other investigations lead to the conclusion, that the active species is a cationic chromium(III)alkyl complex. However, at present we have not enough information about the exact structure of this species in the absence of coordinating solvent molecules.
First published: 28 March 2006
Gesehen am 18.11.2022